2000
DOI: 10.1111/j.1945-5100.2000.tb01978.x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases in iddingsite from the Lafayette meteorite: Evidence for liquid water on Mars in the last few hundred million years

Abstract: Abstract-We analyzed noble gases from 18 samples of weathering products ("iddingsite") from the Lafayette meteorite. Potassium-argon ages of 12 samples range from near zero to 670 * 91 Ma. These ages confirm the martian origin of the iddingsite, but it is not clear whether any or all of the ages represent iddingsite formation as opposed to later alteration or incorporation of martian atmospheric 40Ar. In any case, because iddingsite formation requires liquid water, this data requires the presence of liquid wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 36 publications
5
87
0
Order By: Relevance
“…The secondary aqueous alteration that affected Nakhla is estimated to have taken place on Mars at about 620 Ma (Treiman, 2005, and references therein). Similar ages are also reported for iddingsite in the Lafayette nakhlite (Swindle et al, 2000). This alteration probably occurred rapidly, due to circulation through the Nakhla parent rock of low-temperature hydrothermal fluids, which probably originated from the melted permafrost.…”
Section: Introductionsupporting
confidence: 60%
“…The secondary aqueous alteration that affected Nakhla is estimated to have taken place on Mars at about 620 Ma (Treiman, 2005, and references therein). Similar ages are also reported for iddingsite in the Lafayette nakhlite (Swindle et al, 2000). This alteration probably occurred rapidly, due to circulation through the Nakhla parent rock of low-temperature hydrothermal fluids, which probably originated from the melted permafrost.…”
Section: Introductionsupporting
confidence: 60%
“…However, some clay samples on Earth, with its warmer temperatures, have retained Ar for up to 450 Myr (Dong et al, 1997). Thus, the samples shouldn't have lost their Ar in martian ambient conditions, and Swindle et al (2000) argued that partial gas loss during processing and irradiation is unlikely. Another alternative is that there is not a single age for these weathering products.…”
Section: Timing and Origin Of Aqueous Activitymentioning
confidence: 99%
“…Swindle et al (2000) used a different approach. They extracted individual 1 − 20 µg samples of alteration products from Lafayette and analyzed them using the K-Ar system.…”
Section: The Nakhlite Lafayettementioning
confidence: 99%
“…The second possible explanation for the downward sloping spectra is that these nakhlite samples contain trapped terrestrial atmospheric 40 Ar or martian 40 Ar, not arising from in situ decay (Bogard and Johnson, 1983;Walton et al, 2007;Bogard and Park, 2008), and released primarily at lower temperatures. Trapped martian atmospheric noble gases have been measured in MIL 03346 (Murty et al, 2005;Nagao and Park, 2008) and in other nakhlites (Drake et al, 1994;Gilmour et al, 2001), and at least some of these excess noble gases seem to be associated with martian weathering products (Drake et al, 1994;Swindle et al, 2000). Other workers have demonstrated that noble gases can be incorporated from the terrestrial atmosphere into martian meteorites, including nakhlites, and these may mimic a martian component (Hermann et al, 2006;Schwenzer et al, 2007;Ott, 2008).…”
Section: Cause Of Downward Sloped Age Spectramentioning
confidence: 99%